Influencia De Un Programa De Actividades Motrices En La Capacidad Coordinativa Del Equilibrio En Niños Y Niñas De 6 A 7 Años De La Institución Educativa Santa Teresa De Jesús. (2016)
This investigation is a quantitave research of test and posttest with experimental and control groups; this investigation pretended to stimulate the coordinative capacity of the balance by a program of motor functions’ activities, the data was developed by 36 children, 18 boys and 18 girls on an average between 6 and 7 years old. Taking into account the present theories of RSampieri, C Fernandez, and PBaptista 2010. It’s found that this investigation is a quantitative research because it represents a set of processes, besides, it recollect the data to prove a theory based on a numerical measurement and the analysis is to prove the theories, the design was almost experimental because it consisted on a control group and an experimental group, on the experimental group was applied the variable or the intervention. On the results were established five variables (weight, size, gender, economical situation and age). It showed that the experimental group had similar scores on the test than the control group, the difference lies in the posttest, because the experimental group had a significant improvement in the control group therefore demonstrated significant progress by implementing the program. In conclusion, the program of motor activities of the needs and interests of students; which allowed better, so new, balance, showing the end of the process.